Nuchal translucency and pregnancy outcome. - Kalaivani G,; Shuhaila A,; Rizal AM,; Norzilawati MN, (Department of Surgery, UKM Medical Centre, 2014)
This was a retrospective study done involving 434 patients in a university hospital over period of four years. First trimester ultrasonography were routinely offered for screening of nuchal translucency (NT) at 11 to 13+6 weeks. Morphology scan was performed at 18 to 22 weeks. Pregnancy was followed up till delivery and the information was obtained in all cases by a review of medical records.